no 183. {moltiplicazione 3/10 x 30/4 = 3 x 3 / (1 x 4 ) = 9/4}
radicequadrata[1 + (6/10 + 7/10) : 13/20 - 9/4 + (10/4 + 3/4)] =
= radicequadrata[1 + 13/10 x 20/13 - 9/4 + 13/4] ;
{prima la moltiplicazione 13/10 x 20/13 = 2/1 = 2}.
= radicequadrata[1 + 2 - 9/4 + 13/4] =
= radicequadrata[4/4 + 8/4 - 9/4 + 13/4]=
= radicequadrata[16/4] =
= radicequadrata[4] = 2.
Ciao @sarannn
183)
$\small \sqrt{1+\left(\dfrac{3}{5}+\dfrac{7}{10}\right) : \dfrac{13}{20}-\dfrac{3}{10}·\dfrac{30}{4}+\left(\dfrac{5}{2}+\dfrac{3}{4}\right)}=$
$\small =\sqrt{1+\left(\dfrac{6+7}{10}\right) · \dfrac{20}{13}-\dfrac{3}{\cancel{10}_1}·\dfrac{\cancel{30}^3}{4}+\left(\dfrac{10+3}{4}\right)}=$
$\small =\sqrt{1+\dfrac{\cancel{13}^1}{\cancel{10}_1} · \dfrac{\cancel{20}^2}{\cancel{13}_1}-\dfrac{3}{1}·\dfrac{3}{4}+\dfrac{13}{4}}=$
$\small =\sqrt{1+\dfrac{1}{1} · \dfrac{2}{1}-\dfrac{9}{4}+\dfrac{13}{4}}=$
$\small =\sqrt{1+2-\dfrac{9}{4}+\dfrac{13}{4}}=$
$\small =\sqrt{3-\dfrac{9}{4}+\dfrac{13}{4}}=$
$\small =\sqrt{\dfrac{12-9+13}{4}}=$
$\small =\sqrt{\dfrac{16}{4}}=$
$\small =\sqrt4= 2$